Les relations humains/animaux - Stephanie Chanvallon (Carnets de Géographes, 2013)
Man’s relationship with animal are apprehended with the notion of space: space as a vital safety distance, space proximity under controls, to the intimate and exclusive space during sometimes extraordinary meetings. So under certain conditions space is defined in advance, structured and restrictive, it may be in perpetual construction and development according to the representations and intentions to act, according also to this other animal which flees or approaches, which or not decides not meet the human. When the space shared between these two species is established on a communication and a mutual trust, it acquires another dimension, that of an “animal interval” whose single fitting reflects the relational potentialities.